2018
DOI: 10.1038/s41438-018-0057-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis provides insight into a complex regulatory network of taproot formation in radish (Raphanus sativus L.)

Abstract: The fleshy taproot of radish is an important storage organ determining its yield and quality. Taproot thickening is a complex developmental process in radish. However, the molecular mechanisms governing this process remain unclear at the proteome level. In this study, a comparative proteomic analysis was performed to analyze the proteome changes at three developmental stages of taproot thickening using iTRAQ approach. In total, 1862 differentially expressed proteins (DEPs) were identified from 6342 high-confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 47 publications
2
30
0
Order By: Relevance
“…However, after 120 days under eCO 2 , the activities of the above four sucrose metabolism-related enzymes increased signi cantly in leaves, whereas in fruit tissue, SS and SPS decreased signi cantly, AI increased, and NI showed no change. Sucrose and starch are the major end products of photosynthesis in most plants and they are also major carbon sources involved in the synthesis of other important structural and metabolic compounds, such as cellulose and proteins, respectively [27,38,39]. Additionally, only two types of enzyme can cleave sucrose in plants: sucrose invertase, and sucrose synthase (SS) [40].…”
Section: Regulatory Transformation Of Sugar and Related Enzymesmentioning
confidence: 99%
“…However, after 120 days under eCO 2 , the activities of the above four sucrose metabolism-related enzymes increased signi cantly in leaves, whereas in fruit tissue, SS and SPS decreased signi cantly, AI increased, and NI showed no change. Sucrose and starch are the major end products of photosynthesis in most plants and they are also major carbon sources involved in the synthesis of other important structural and metabolic compounds, such as cellulose and proteins, respectively [27,38,39]. Additionally, only two types of enzyme can cleave sucrose in plants: sucrose invertase, and sucrose synthase (SS) [40].…”
Section: Regulatory Transformation Of Sugar and Related Enzymesmentioning
confidence: 99%
“…XTH9, XTH7), and root cell elongation factor (e.g. COBRA) [35,39], which might determine cell size during taproot thickening. In addition, several transcription factors (TFs) were found to be involved in root development in other plants including rice, and Arabidopsis, and some TFs including bHLHs (e.g.…”
Section: Molecular Dynamic Regulation Network Of Taproot Formation Anmentioning
confidence: 99%
“…Meanwhile, CDC5 gene was crucial to cell cycle during the G2 period, and the phase transition of G2 to M (G2/ M) was affected in the AtCDC5-RNAi transformants [37], and AtCDC5-VIGS transformants died before bolting and accelerated cell death [38]. Interestingly, CDC5 was identified to be up-regulated during taproot thickening, whatever RNA-seq or iTRAQ-seq method, which would be play important role in cell division of taproot thickening in radish [13,35]. In this study, RT-qPCR validation result was approximately consistent with those of previous studies, and CDC5 showed high abundance expression at ES (Fig.…”
Section: Sus1 and Cdc5 Might Contribute To Taproot Thickening In Radishmentioning
confidence: 99%
“…Root shape and size are important traits that can influence the commercial quality of radishes, such as transportation efficiency, processing methods, and consumer appeal. Studies on radish tuberous root formation have been a hot topic recently, and have mainly focused on finding QTLs, differentially expressed genes or proteins related to storage root formation [5][6][7][8][9][10][11]. However, the developmental mechanisms underlying the beneficial alleles controlling root formation have not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%